Paint brush hair: a case report - Munusamy, Rajesh; Sekar, Aishwarya Lakshmi (International Journal of Research in Dermatology, 2021)
Trichorrhexis nodosa (TN) is an hair shaft disorder presenting with whitish nodes all over the hair (diffuse form) or localized to an area (localized form) and could be either congenital or acquired. TNis ultimately a response to physical or chemical trauma that leads to formation of nodes along the hair shaft. Here, we reported a case of TNof the beard, diagnosed clinically and through trichoscopy. Patient was advised to shave his beard hair and to avoid brushing completely. On follow-up, the patient was symptomatically better. Based on this, TNof the beard was confirmed.